Dietary calcium intake was related to the onset of pre‐eclampsia: The TMM BirThree Cohort Study. Issue 1 (28th December 2022) - Ohseto, Hisashi; Ishikuro, Mami; Obara, Taku; Murakami, Keiko; Onuma, Tomomi; Noda, Aoi; Takahashi, Ippei; Matsuzaki, Fumiko; Ueno, Fumihiko; Iwama, Noriyuki; Kikuya, Masahiro; Metoki, Hirohito; et al.
Abstract: This study aimed to explore the relationship between dietary electrolyte intake and the prevalence of hypertensive disorders of pregnancy (HDP) subtypes. Our analysis included 19 914 pregnant women from the Tohoku Medical Megabank Project Birth and Three‐Generation Cohort Study. A food frequency questionnaire was used to estimate dietary calcium, potassium, sodium, and magnesium intakes. HDP was determined based on the medical records during regular antenatal care. Logistic regression analysis assessed the relationship between dietary electrolytes intake quintiles, and HDP subtypes with adjustment for basic characteristics. Dietary electrolyte intakes were applied for the prediction model. Of the cohort, 547 participants delivered with pre‐eclampsia (PE), 278 with superimposed PE (SP), and 896 with gestational hypertension (GH). PE was associated with low crude calcium intake (odds ratio of the first quintile [<251 mg/day] to the fifth quintile [>623 mg/day] and 95% confidence interval, 1.31 [1.00–1.70]) and P for trend was .02. SP was not associated with any nutritional intake; however, the combined outcome of PE and SP was related to low crude calcium and potassium and energy‐adjusted calcium, potassium, and magnesium intakes ( P for trend, .01, .048, .02, .04, and .02, respectively). The same tendency was observed for GH. A prediction model that included crude calcium and potassium intakes performed better than a model without them. In conclusion, low dietary calcium, potassium, and magnesium were associated with higher HDP subtypes prevalence. The prediction model implied that crude calcium and potassium intakes might play a critical role in PE and SP pathogenesis.